Re-defining stewardship : a Nigerian perspective on accountable and responsible land ownership according to the Old Testament - Ahiamadu, Amadi (Stellenbosch : Stellenbosch University, 2008)
Thesis (DTh (Old and New Testament))--Stellenbosch University